COVID-19 Susceptibility and Outcomes Among People Living With HIV in San Francisco. (1st January 2021) - Sachdev, Darpun; Mara, Elise; Hsu, Ling; Scheer, Susan; Rutherford, George; Enanoria, Wayne; Gandhi, Monica
Abstract : Introduction: Studies to examine whether HIV predisposes to a higher incidence of COVID-19 or more severe disease are accumulating. Initial studies from New York City suggested more severe disease among people living with HIV (PLWH), but this was during a time when hospitals were over-capacity and health systems stretched. This report presents the incidence and outcomes among PLWH with COVID-19 in San Francisco over the first 6 months of the pandemic. Methods: Community transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was first reported in San Francisco on March 5, 2020. This report examines the match of the San Francisco Department of Public Health COVID-19 testing database and the San Francisco Department of Public Health HIV Surveillance case registry from March 24, 2020, to September 3, 2020. Results: Among 4252 COVID-19 tests performed among PLWH, 4.5% (N = 193) were positive for COVID-19, compared with a 3.5% (N = 9626) positivity rate among the 272, 555 people without HIV tested for COVID-19 ( P < 0.001). The mean age of those infected with HIV/COVID-19 was 48 years (20–76), 38.9% White, 38.3% Latinx, 11.9% Black, and 91.2% were men. Only 54.6% of coinfected PLWH were housed, with the remainder marginally housed. The rate of severe illness with COVID-19 was not increased among PLWH. Discussion: In San Francisco, susceptibility to COVID-19 was increased among PLWH over the first 6 months of the pandemic, although clinical outcomes were similar to those without HIV. Homelessness and higher rates of congregate living situations among PLWH likely accounted for this disparity. Special efforts to house patients with marginal housing during the COVID-19 pandemic are needed.